Searches of the periods and variability type definition of new variable stars AL Ari, FM Leo, LL Aqr, V1125 Tau, V1366 Ori - Solonovich, A. P.; Bryukhanov, I. V.; Sernenyuta, A. S. (Одеські астрономічні публікації, 2017)
Measurements of brightness of stars 1AL Ari, FM Leo, LL Aqr, V1125 Tau, V1366 Ori opened in ”HIPPARCOS” experiment are carried out using negatives of the Odessa observatory. The authors classify all these stars to be EA type-variables With ephemerids 2448163.549+3.7474335E (AL Ari), 2448202.975+3.3643328E (FM Leo), 2439359462 + 94.597E (LL Aqr), 2445699335 + 8.5912498E (V1125 Tau) and 2444986278 + 15.7298348E (V1366 Ori).